Hubungan Dukungan Teman Sebaya dengan Tingkat Stres Akademik Siswa di Sma Negeri 4 Denpasar Tahun 2026 - Dhea Putri Salsalbillah; I Dewa Ayu Eka Purba Dharma Tari; I Wayan Juliawan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This quantitative correlational study aims to determine the relationship between peer support and academic stress levels in 12th-grade students at SMA Negeri 4 Denpasar in the 2025/2026 academic year, driven by the high academic demands placed on final-year students. Using the Pearson Product Moment correlation technique through SPSS on a sample of 204 students, data collection was conducted using the Peer Support Scale (44 items; α = 0.935) and the Academic Stress Scale (34 items; α = 0.874). The results of the descriptive analysis indicate that the majority of students fall into the moderate peer support category (75.98%) and the moderate academic stress level (73.53%). Hypothesis testing revealed a significant and strong positive relationship between the two variables (r = 0.611; p < 0.001), meaning that the higher a student's academic stress level, the higher the activation of social support from peers as a form of psychological buffer. With a 37.3% effect (R2 = 0.373), these results provide an empirical basis for Guidance and Counseling (BK) teachers to design preventive group interventions to build a supportive school ecosystem for student mental well-being.